THE EXPERT SYSTEM OF CONTROL AND KNOWLEDGE ASSESSMENT - V. Golovachyova (Astana IT University, 2020)
The article deals with the problem of objective knowledge assessment using expert automated systems for monitoring and evaluating knowledge. The expert systems of control and knowledge estimation are usually developed on the basis of different approaches to constructing a question and answer on test. The analysis of existing testing methods made it possible to conclude that questions with selective and selectively constructed types of answer do not always allow objectively assessing the knowledge of trainees, which reduces the stimulating effect of pedagogical evaluation on cognitive activity of trainees, and the quality of the learning process as a whole. The article proposes a method of knowledge estimation, which is based on a new approach to constructing a question and answer that allows a freely designed form of a test response. Such answer is analyzed by a set of criteria for its formation based on the developed algorithms for the criteria for assessing their quality. This makes it possible to apply the obtained results to solve the scientific problem of objective knowledge assessment using testing. The proposed approach gives an opportunity to expand the functions of tests, thereby increasing the approximation degree of the estimation for the test to the level of the real knowledge of students. The purpose of the article is to justify the effectiveness and develop the expert system of control and knowledge assessment. The article is addressed to a wide range of researchers and experts in the field of education and information technologies.